Instruments supporting revitalization activities and their impact on the activation of degraded spatial arrangements, illustrated with examples of Wroclaw, Lodz and Cracow - Świerczewska-Pietras, Katarzyna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2010)
The paper aims at analysing instruments supporting revitalization activities and their impact on the transformation of degraded spatial structures of Wrocław, Łódź and Cracow. These instruments include documents of Local Revitalization Programmes, management and implementation strategies, as well as strategies of monitoring crisis areas, financing instruments in the form of the European Union funds, and works on a revitalization act.